PENGARUH KETINGGIAN BAK PENANGKAP AIR DAN PANJANG PIPA MASUK TERHADAP HEAD PUMP PADA POMPA HIDRAM - Utomo, Gatut Prijo; Arifianto, Muhamad (MEKANIKA: Jurnal Teknik Mesin, 2015)
Dusun Ketos and Dusun Cabe is 2 (two) of 7 (seven) Dusun in Kulon Wonodadi Ngadirojo Pacitan, EastJava. The problems faced by the community, especially for Ketos Dusun and Dusun Cabe whose territory the formof hills and rocks are prone / difficulty of clean water, clean water to meet the needs of the people using water fromsprings and rainwater. In the dry season, water from springs debitnya reduced, so that less water needs in thevillage. Only water can not be drained using gravity because it is under the township residents located on the hill - ahill at an altitude of 750 m above sea level. The approach offered to solve the problem is by making a catchmentbasin, hydraulic ram and tank water divider.The effectiveness of the performance of hydraulic ram is influenced by several parameters, among others: the lengthof the inlet pipe, inlet pipe diameter, high penagkap tub of water, and heavy exhaust valve. This study aims toobserve and analyze the effect of altitude penagkap tub of water and a long inlet pipe to the pump head on thehydraulic ram. The research method through designing hydraulic ram and analyzing the catchment basin height of2.9 m, 3.2 m and 3.5 m and a length of inlet pipe 18 m, 24 m and 30 m. Tests carried out in the river, precisely inDusun and Dusun Ketos Cabe, Pacitan.Based on the research and analysis it can be concluded that by using the height of basin catchment 3.5 m and 30 mlength of pipe entry could generate more volume and maximum pressure compared with other tests and can producewater flow of up to 6.7 L / min at pump head 173 m with a vertical condition.So the higher the basin catchment (H), the greater the discharge of the hydraulic ram and the pressure generated inthe intake also getting bigger, while for long inlet pipe (L), the length of the pipe entering the greater the volumeand pressure of entering into Conductor flowing through the valve body hidram, because the water is very largeimpulse will open the waste valve and the valve closed waste arrived - arrived to make the flow greater impetus.This is because water is the greatest moment of the collision on H 3.5 m and 30 m L it affect the discharge resultsand the hydraulic ram pump head.Keywords: hydraulic ram, high penagkap tub of water, the length of the pipe entrance